The Influence Of The Creative Problem Solving (CPS) Model on Science Learning Outcomes in Terms Of Students' Multicultural Attitudes - Wapa, Andi; Arnyana, Ida Bagus Putu; Suastra, I Wayan (Universitas Lampung, 2024)
The population in this study were all sixth grade elementary school students in Gugus II Ledokombo who implemented K13 with a total of 334 students. The sample consisted of 120 students who were divided into two experimental classes and two control classes using group random sampling technique. The instruments used were science learning outcomes tests and multicultural attitude questionnaires. Data analysis was carried out using ANOVA. The results of this research show that: Testing the first hypothesis, the null hypothesis was rejected and the alternative hypothesis was accepted (analysis results: